Implementation of Salibu Rice Cultivation Technology in Percut Sei Tuan Sub-District - Mayly, Syarifa; Syafri, A (Talenta Publisher Universitas Sumatera Utara, 2018)
Percut Sei Tuan Sub-district is an agricultural production center in Deli Serdang Regency. The area of irrigated paddy field in Percut Sei Tuan Sub-district comprises of 3,610 ha and 1,616 ha of non-irrigated paddy field. The farmer association groups (tani mitra) consisting of Farmer Group